THE RELATION BETWEEN LEARNING INTEREST, PARENTAL INVOLVEMENT AND ANXIETY TOWARD MATHEMATICS LEARNING OUTCOMES - Amanatun Salasiyah; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Students' learning outcomes may depend on several factors. It is assumed that learning interest, parental involvement, and anxiety are related to the students' learning outcomes. This research aims to know whether there is a positive and significant relationship between learning interest, parental involvement, and anxiety and mathematic learning outcomes of grade VIII students in the odd semester of SMP Cokroaminoto Wanadadi, Banjarnegara Regency, in the academic year of 2016/2017. The populations of this research are 95 students in grade VIII of SMP Cokroaminoto Wanadadi, Banjarnegara Regency, in the academic year of 2016/2017, consisting of grade VIII A, VIII B, and VIII C. Grade VIII B students were taken as the sample through random sampling class. The data were collected using a questionnaire, which is useful to obtain the data on the learning interest, parental involvement, and anxiety in mathematics. Besides, a test was also carried out to get the data on the learning outcomes in mathematics. The instrument was tested using a validity test, differential test, and reliability test. Prerequisite analysis tests include normality tests, linearity tests, and independence tests. The data were analyzed using product moment analysis and multiple linear regressions. The research findings indicate that there is a significant relationship between learning interest, parental involvement, as well as anxiety and mathematics learning outcomes of grade VIII students in the odd semester of SMP Cokroaminoto Wanadadi Banjarnegara regency in the academic year of 2016/2017. It can be seen from the results showing that Fcount>Ftablethat is 10.022 > 2.95 with R = 0.7196 and R2 = 0.51780 with Y= 29.5269 + 0.5797 X1+ 0.1417 X2– 0.2878X3, with Relative Contribution X1 = 77.7748%, Relative Contribution X2 = 9.9445%,and Relative Contribution X3 = 12.2807%, SE X1 = 40.2718%, Effective Contribution X2 = 5.1492%, and Effective Contribution X3 = 6.2590%.